KAJIAN SOSIO-RELIGIUS PENERAPAN SANKSI ADAT KANORAYANG DI DESA PAKRAMAN BAKBAKAN KECAMATAN GIANYAR, KABUPATEN GIANYAR - Eka Suadnyana, Ida Bagus Putu; Yuniastuti, Ni Wayan (WIDYANATYA, 2019)
Pakraman Bakbakan Village is one of the areas in the Balinese customary law area which also has regulations governing the lives of its people which are basically poured into awig-awig forms that are generally owned by all Pakraman Villages in Bali. In awig-awig, Pakraman Bakbakan Village, there is one adat sanction, namely Kanorayang adat sanction which is still preserved. The application of Kanorayang customary sanctions is based on awig-awig Desa Pakraman Bakbakan Palet Kaping XX (Indik Pamidanda). The imposition of Kanorayang adat sanctions is applied as an act of expulsion from Pakraman village customary activities so that those who are subject to the kanorayang adat sanctions lose their rights and obligations within the Pakraman Village organization. For those who are subject to customary sanctions in the village of Pakraman Bakbakan will not be able to use traditional facilities such as the temple of heaven, setra or grave, infrastructure owned by the Pakraman village (wantilan, village bale, aykul kulkul, etc.). This study uses a qualitative research design through an ethnographic case study approach with an emphasis on critical and interpretive studies without ignoring the study of empirical elements. By collecting data through sampling techniques, where in this study is purposive sampling through people who are considered key (key person) and understand about the application of customary sanctions in the village of Pakraman Bakbakan Pakraman. This research can be used as a critique and suggestion so that in the process of implementing customary sanctions the canor does not deviate from the objectives of customary law itself. And with the existence of customary sanctions in the village of Pakraman Bakbakan is expected to maintain harmony and in an atmosphere of "paras-paros, gilik-saguluk, salunglung-sabayantaka".